Enhancing health care non‐technical skills: the TINSELS programme. (15th July 2015) - Gordon, Morris; Box, Helen; Halliwell, Jo‐Anne; Farrell, Michael; Parker, Linda; Stewart, Alison
Summary: Background and context: Training in 'non‐technical skills', i.e. social (communication and teamwork) and cognitive (analytical and personal behaviour) skills, in health care have been of great interest over the last decade. Whereas the majority of publications focus on 'whether' such education can be successful, they overlook 'how' they enhance skills. We designed and piloted a theoretically robust teaching package that addresses non‐technical skills in the context of medicine safety through simulation‐based interprofessional learning: the Training In Non‐technical Skills to Enhance Levels of Medicines Safety (TINSELS) programme. Innovation: A modified Delphi process was completed to identify learning outcomes, and multi‐professional teams were recruited through local publicity. The faculty staff developed a three‐session simulation‐based intervention: firstly, a simulated ward encounter with multiple medicine‐related activities; secondly, an extended debriefing and facilitated discussion; and finally, a 'chamber of horrors', where interprofessional teams identified potential sources of error. Each session was completed in the simulation suite with between six and nine participants, lasted approximately 90 minutes and took place over 2 weeks. Full details of the course will be presented to facilitate dissemination. Training in 'non‐technical skills' in health care have been of great interest over the last decade Implications: Feedback was collected on a Likert scale after the course (1, strongly disagree; 5, strongly agree). Mean scores were all greater than 4, with qualitative feedback noting the fidelity of the authentic interprofessional groups. A previously validated safety attitudes questionnaire found changes in attitudes towards handover of care and perceptions of safety in the workplace. An original, simulation‐based, multi‐professional training programme has been developed with learning and assessment materials available for widespread replication.